Pengaruh Return On Investment Dan Earning Per Share terhadap Harga Saham (Studi Pada Perusahaan Perbankan Swasta yang Go Public dan Terdaftar di BEI) - Noor Rokhman, M. Taufiq (Arthavidya Jurnal Ilmiah Ekonomi, 2014)
Return On Investmet is one form of profitability ratios whichare intended to measure the overall ability of the company with fundsinvested in assets that are used for company operations (net operatingincome) by the amount of investment or asset. While earnings per shareis earnings per share of the company being sold. EPS obtained fromdividing the profit after tax by the number of shares. The results showedthat both individually and jointly Return on Investment (ROI) andearnings per share (EPS) have a significant influence on stock prices ofprivate banking company listed in Indonesia Stock Exchange.Suggestions research variables used in this study there are only twoindependent variables that affect stock prices, expected future studies toexamine more variables.Keyword: Return on Investment (ROI), Earnings Per Share (EPS),influence on stock prices of private banking company listed inIndonesia Stock Exchange.